Examining the influence of port ship activities on pollutant emissions in port environments - Xinjia Gao; Qifeng Yu; Wei Dai; Qinyang Chen (Heliyon)
There is a direct and close relationship between ship emissions in port waters and the operational status of the ships. Precisely identifying the operational status of ships in port waters and thoroughly exploring the specific relationship between these activities and ship emissions is crucial for achieving accurate control and scientific reduction of emissions from ships in port areas. With advancements in technology, AIS data can accurately capture the operational status of ships, facilitating a macro-level analysis of ship behavior and emission characteristics. This study proposes a method for extracting ship activity states using AIS data and conducts a detailed examination of ship activities at various container terminals and berths within Shanghai Port. Additionally, it analyzes the correlation between ship activities and their emissions. The research findings indicate that container ships are the most prevalent ships at Shanghai Port, followed by bulk carriers, general cargo ships, and tankers. Notably, bulk carriers and tankers exhibit the longest berthing times, with tankers showing the most significant fluctuations. Mingdong Terminal is identified as the most active, featuring the longest anchorage and berthing time, whereas Jungonglu and Zhanghuabang Terminals have the shortest. The calculation of pollutant emissions reveals that container ships and oil tankers are the primary contributors, particularly for CO2 and NOx emissions. Mingdong Terminal recorded the highest total CO2 emissions, followed by Guandong and Shengdong Terminals. These findings emphasize the importance of berth service efficiency, suggesting that increased emissions are associated with heightened ship activity. CO2 emissions from container ships increase linearly with the number of berthed ships and show a cubic nonlinear relationship with berthing time. The analysis highlights terminals such as Guandong, Zhendong, Shengdong, and Yangshan Phase IV as critical areas for emission reduction strategies. This study not only enhances our understanding of the dynamics of ship emissions in port waters but also provides a theoretical foundation for implementing effective emission control and reduction strategies. Through this detailed research approach, it is possible to more accurately identify emission sources and optimize port operations, thereby offering strong data support and scientific guidance for environmental management and policy-making in port waters.